2022
DOI: 10.1016/j.cmi.2021.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis after allogeneic haematopoietic cell transplantation: experience using a PCR-guided pre-emptive approach

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Despite the high prevalence of anti- Toxoplasma IgG positivity (58.3% of alloHSCT recipients), toxoplasmosis was infrequent in our 10 year-long study, with 0.56% and 3.5% of our patients diagnosed with Toxoplasma disease and infection, respectively. The present prevalence of Toxoplasma reactivation (4.13%) is close to the prevalence reported in the most recent studies (3.9-4.1%) (8,17,18), whereas older studies reported higher figures, from 8.7 to 18.6% (5,7,1921). This decrease can be ascribed to the decrease of seroprevalence of anti- Toxoplasma antibodies in the general population (22).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Despite the high prevalence of anti- Toxoplasma IgG positivity (58.3% of alloHSCT recipients), toxoplasmosis was infrequent in our 10 year-long study, with 0.56% and 3.5% of our patients diagnosed with Toxoplasma disease and infection, respectively. The present prevalence of Toxoplasma reactivation (4.13%) is close to the prevalence reported in the most recent studies (3.9-4.1%) (8,17,18), whereas older studies reported higher figures, from 8.7 to 18.6% (5,7,1921). This decrease can be ascribed to the decrease of seroprevalence of anti- Toxoplasma antibodies in the general population (22).…”
Section: Discussionsupporting
confidence: 85%
“…Asymptomatic qPCR-positive patients receiving prophylaxis (n= 9) or not (n= 2) became negative on a following sample, before any treatment change or implementation. This can be expected according to Poisson’s law in case of a parasitic load at the limit of detection of the qPCR, assuming that there are no technical false positive PCR results, and can support the choice to wait for a second positive result before starting anti- Toxoplasma treatment, as proposed by Aerts et al (17). In case of a negative control qPCR, the hypothesis would be that these patients have cleared the infection, thanks to anti- Toxoplasma immune recovery.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations